Social Validity in Early Language Interventions for Dual Language Learners: A Systematic Review of the Literature. (May 2020) - Larson, Anne L.; An, Zhe Gigi; Wood, Carla; Uchikoshi, Yuuko; Cycyk, Lauren M.; Scheffner Hammer, Carol; Escobar, Kelly; Roberts, Kate
The social validity of intervention research has been emphasized in special education and related fields for decades. There is relatively little focus on social validity that considers culturally and linguistically diverse populations. Eleven articles met the inclusionary criteria for this systematic review and were evaluated to describe social validity in early language intervention research—specifically with young (birth through 5 years) dual language learners (DLLs). We examined how social validity was considered and addressed, how social validity was measured, and the results of social validity assessments. Definitions of social validity were generally vague, and researchers in most studies only considered social validity post intervention rather than prior to starting or during the interventions. Participants generally viewed interventions positively, but incomplete data were often reported.